CASE STUDY: ACTIVE LEARNING TEACHING METHOD FOR COURSES IN FINANCIAL MANAGEMENT - BUSMACHIU, Eugenia; SAUNDERS, Kent T. (Acta et Commentationes, Sciences of Education, 2022)
The use of case studies is an active learning teaching method that enables students to apply and analyze course material. The focus of the described case is cash flow estimation for a new project, capital budgeting decision. The case is designed to specifically consider the effects of changing exchange rates and determine ways to mitigate exchange rate risk. This case study includes discussion questions related to objectionable business activity, weighted average cost of capital, cash flow estimation, net present value calculation, exchange rate risk, and sensitivity analysis. This case is appropriate for both undergraduate and graduate courses in financial management. Additionally, this case can be used in courses in entrepreneurial finance.